Evaluation of the ESP Culture System II for Testing Susceptibilities of Mycobacterium tuberculosis Isolates to Four Primary Antituberculous Drugs - Bergmann, John S. (American Society for Microbiology, 1998)
The reliability of the ESP Culture System II (herein referred to as ESP II) for testing susceptibilities of Mycobacterium tuberculosis isolates to isoniazid, rifampin, ethambutol, and streptomycin was evaluated by comparing results to those of the method of proportion (MOP), which was considered the reference method, for 20 clinical isolates and 30 challenge strains provided by the Centers for Disease Control and Prevention (CDC). Clinical isolates also were tested with the BACTEC TB 460 system; these results agreed with those obtained by the MOP for all isolates and all drugs, except the high concentration of isoniazid, for which agreement was 95%. After resolution of discrepancies, levels of agreement between ESP II and MOP for the clinical isolates were 95 and 100%, respectively, for the low and high concentrations of isoniazid, 100% for rifampin and ethambutol, and 95% for streptomycin. For the 30 challenge isolates, ESP II results for both concentrations of isoniazid agreed with the expected results in all cases, whereas agreement was 93% for both rifampin and streptomycin and 90% for ethambutol. All discrepancies with the CDC isolates were due to failure of ESP II to correctly classify resistant strains. By testing isolates yielding discrepant ethambutol and streptomycin results with a lower concentration of both drugs in the ESP II system, agreement increased to 93% for ethambutol and 100% for streptomycin. For the clinical isolates, the times to an ESP II result of susceptible (means ± standard errors of the means) were 8.47 ± 0.12 days (range, 7 to 10 days) and 8.73 ± 0.29 days (range, 5 to 11 days) when the inoculum was prepared from a McFarland equivalent and from a seed bottle, respectively. The time to an ESP II result of resistant varied by drug and method of inoculum preparation, ranging from 5.50 ± 0.22 days for ethambutol with the inoculum prepared from a McFarland standard to 8.0 days for ethambutol with the inoculum prepared from a seed bottle. These data suggest that the ESP II system is a rapid and reliable method for testing susceptibilities of M. tuberculosis isolates to isoniazid and rifampin. Performance, however, may be suboptimal for ethambutol and streptomycin. Testing additional ethambutol-resistant and streptomycin-resistant strains with two concentrations of both drugs is necessary.